2009
DOI: 10.1007/s11250-009-9441-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of quality of beef produced and sold in parts of Tigray Region of Ethiopia

Abstract: Microbiological and physical quality of 83 samples of beef produced and marketed in some parts of Tigray region of Ethiopia were evaluated. The color, marbling, pH, bleeding status and aerobic plate count (APC) were within permissible limits in 35(42.16%), 47(56.63%), 51 (61.44%), 13(15.66%) and 20(24.09%) samples, respectively. Based on these parameters, a high percentage of samples (varying from 38.56%-84.34%) were of unsatisfactory quality. Such a widespread imperfect bleeding (84.34%) and high APC (75.91%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…32.5% of samples (176) were positive for S. aureus in cattle and pigs slaughtered in selected abattoirs in South Africa, according to Nicoline et al (2015), which corroborates with this study. The results about total areobic mesophilic bacteria and Enterobacteriaceae in different samples of meat were similar to the results reported by Kumar et al (2010) for raw beef meat marketed in some parts of Tigray region (Ethiopia). The higher levels of TAM bacteria and Enterobacteriaceae in various types of meat (Table 1) may also be due to the fact that meat offers a rich nutrient media for microbial growth (Nfor et al, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…32.5% of samples (176) were positive for S. aureus in cattle and pigs slaughtered in selected abattoirs in South Africa, according to Nicoline et al (2015), which corroborates with this study. The results about total areobic mesophilic bacteria and Enterobacteriaceae in different samples of meat were similar to the results reported by Kumar et al (2010) for raw beef meat marketed in some parts of Tigray region (Ethiopia). The higher levels of TAM bacteria and Enterobacteriaceae in various types of meat (Table 1) may also be due to the fact that meat offers a rich nutrient media for microbial growth (Nfor et al, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…This would further contaminate the carcasses and compromise the quality of meat. This might be the reason for poor quality of beef reported at local markets in Ethiopia (Kumar et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Personnel at the abattoirs did not wear clean aprons, clothing, boots, mesh gloves and hair caps during meat processing. This might be the reason for high aerobic plate count (APC) in beef sold at local markets in Ethiopia (Kumar et al, 2010). For good hygienic practices and production of high quality meat, workers should ensure their hands are always clean, and also wear clean protective clothing to cover both their body and hair.…”
Section: Discussionmentioning
confidence: 99%
“…Out of the total 26 abattoir workers interviewed, 7.7% of them were illiterate. 61.5% of the respondents did not take training regarding meat hygiene.…”
Section: Educational Status Of Abattoir Workers and Training Of Meat mentioning
confidence: 99%
“…Bacterial contamination of meat products is an unavoidable consequence of meat processing [3] . Even if data regarding meat borne diseases in Ethiopia are extremely scarce, a few studies conducted in different parts of the country have shown the public health importance of several bacterial pathogens associated with foods of animal origin [4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%